Speaking the Unspeakable : Allen Ginsberg's Paradigm of Prophetic Poetry - Faust, Jonas, (Beiträge zur englischen und amerikanischen Literatur ;, 2025)
Allen Ginsberg (1926-1997), one of the most important and widely read American poets of the 20th century, depicted himself as the prophet of a new America. Scholars and critics have echoed this self-description and turned prophecy into a key theme of his life, but their understanding of this notion often remains vague and ill-defined. Speaking the Unspeakable constructs a flexible definition of prophecy from the poet's own perspective and applies it to his entire work chronologically to capture its developments, idiosyncrasies and tensions. In addition, it applies Bourdieu's cultural sociology to explore how Ginsberg used his self-depiction to situate himself in the literary field of postwar America and claim a position at the forefront of the avant-garde in the transitioning period from modernism to postmodernism. Ginsberg's esoteric seeker religiousness and his exuberant claims to epiphanic experiences are intricately linked, as this study shows, to his literary success.